Chemical diversity and mode of action of natural products targeting lipids in the eukaryotic cell membrane. Issue 5 (5th February 2020) - Nishimura, Shinichi; Matsumori, Nobuaki
Abstract : This review article focuses on natural products that bind to eukaryotic membrane lipids, and includes clinically important molecules and key research tools. How their mechanism was unveiled, and how they are used in research are also mentioned. Abstract : Covering: up to 2019 Nature furnishes bioactive compounds (natural products) with complex chemical structures, yet with simple, sophisticated molecular mechanisms. When natural products exhibit their activities in cells or bodies, they first have to bind or react with a target molecule in/on the cell. The cell membrane is a major target for bioactive compounds. Recently, our understanding of the molecular mechanism of interactions between natural products and membrane lipids progressed with the aid of newly-developed analytical methods. New technology reconnects old compounds with membrane lipids, while new membrane-targeting molecules are being discovered through the screening for antimicrobial potential of natural products. This review article focuses on natural products that bind to eukaryotic membrane lipids, and includes clinically important molecules and key research tools. The chemical diversity of membrane-targeting natural products and the molecular basis of lipid recognition are described. The history of how their mechanism was unveiled, and how these natural products are used in research are also mentioned.